The talking drums of the Yoruba - Beier, Ulli (International Library of African Music, 1954)
The most common type of Talking Drum among the Yoruba is called “Dundun” (see Plate I). Europeans sometimes refer to it as an hourglass-drum, because of its shape. It has two membranes, of which only one is beaten, however. The leather strings connecting the membranes are gripped by the drummer’s left hand, and by tightening them, he can raise the pitch of the drum. There are many kinds of Dundun drums, but the most important one is called “Lya-Ilu” (mother of the drums) which has a range of about an octave - the exact range depending on the strength of the drummer.
Keywords: Talking drum; Yoruba (African people); Music; Musical instruments; Laudatory poetry; Percussion instruments; Drum; Drum language; Nigeria; African Music; Yoruba Art; Drum (Instrument); Talking Drum (Instrument)